Delays in HIV and TB diagnosis and treatment initiation in co-infected patients in Colombia. (April 2020) - Ríos-Hincapié, Cielo Yaneth; Rojas, Marcela; López, Martha; Porras, Alexandra; Luque, Ricardo; Pelissari, Daniele Maria; López, Lucelly; Rueda, Zulma Vanessa
We investigated the delays in the diagnosis of tuberculosis and/or HIV, their treatment initiation, and factors associated with each delay. All drug-susceptible tuberculosis cases diagnosed in 2014 and 2015 in Colombia, with a confirmed diagnosis of HIV were included. A total of 1909 patients were registered with tuberculosis/HIV co-infection. Seventy-nine percent of patients were men, 50% had sputum smear-negative tuberculosis, culture was done in 50% of cases, 68.5% had <200 CD4 cell count at diagnosis, and 35% had concurrent tuberculosis/HIV diagnosis. Delays in the tuberculosis diagnosis were identified in 54.8% of the patients, and delays in tuberculosis and HIV treatment initiation in 41.8% and 27.4%, respectively. The risk factors associated with delay in tuberculosis diagnosis were age between 15–34 and ≥45 years, and those patients who received tuberculin skin test. The risk factor associated with antiretroviral therapy initiation delay was previously-treated tuberculosis patients after failure. It is necessary to implement strategies for early detection and treatment initiation of HIV and to use rapid test for tuberculosis diagnosis in this population.